Gabon : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses challenges, outlook, and risks of Gabon's economy. Gabon's economy is facing mounting headwinds. Economic activity benefited from a one-off boost in oil production in 2015, due to the introduction of new oil fields and productivity improvements, which are expected to help maintain overall growth about 4 percent in 2015. However, the slowdown in non-oil economy activity continued, led by construction, transport, commerce, and services. The main downside risk to the outlook remains weak fiscal adjustment to sharply lower oil prices. In the event of weaker-than-projected performance on oil revenues or government spending, government would be forced to substantially draw down on its deposit buffer and/or significantly increase borrowing.